Income Concentration in the Southern United States - Farbman, Michael (The Review of Economics and Statistics, 1973)
M UCH work has been done on the many aspects of the size distribution of income. This includes a large body of literature purporting to explain variations in this phenomenon both temporally and spatially for large geographic units in terms of different and/or changing functional distributions of income (Kuznets, 1953), differential growth rates (Kravis, 1960; Kuznets, 1955), random or stochastic processes (Champernowne, 1963; Gibrat, 1931; Rutherford, 1955), and combinations of economic, social and demographic factors (Aigner and Heins, 1967; Al-Samarrie and Miller, 1967). Conspicuously absent from the literature, however, is any empirical work done on variations in the size distribution of income in small areas, either over time or over space. The omission of time-series analysis of variations among small area income distributions is due largely to the unavailability of small area personal income statistics for all but decennial census years. No such excuse may be offered for the absence of cross-sectional analysis, inasmuch as the last three decennial censuses (1950, 1960 and 1970) have provided data for regions and small areas on a comparable basis. It would appear, however, that published empirical research on size distribution of income in small areas has tended to concentrate more on the nonsubstantive statistical questions such as the identification of ''proper area definitions and less on inter-area variations than is true of inter-state and international income distribution studies which by and large have tended to avoid facing the former issue squarely, or merely assumed that it was irrelevant. This paper will draw together these heretofore unjoined aspects of the study of income distribution. In it we shall construct and test an analytical model for explaining variations in the degree of income concentration among small spatial units in terms of various economic, social and demographic variables which are thought for a priori reasons to be influential. We shall draw upon the approaches of similar studies while modifying them for our own ends, keeping in mind also that our aim is not to verify any single hypothesis such as economic growth or development vis-a-vis income distribution, but to isolate and quantify the influence of a broad group of causal factors which operating simultaneously may determine the degree of concentration of family incomes within a spatial area. Not only will it be shown that the economic and social factors most highly associated with spatial variations in income inequality can be positively identified for small areas, but what is more important, these will be shown to vary over space in relative impact as well as varying in importance according to level of aggregation of the observation unit.